HIGH COMMITMENT MANAGEMENT AND ITS IMPACT ON IMPROVING THE COMPETITIVE ADVANTAGE OF A SAMPLE OF SOME PHARMACEUTICAL COMPANIES IN BAGHDAD - ASSIST. LECTURER. SAIF ALI KAMIL, Dr. ZAHRAA GHANIM MIRJAH, Dr. QASIM ALI MOHAMMED, Dr. ABDULKAREEM MEZAAL TAHER (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to analyze the impact of the dimensions of high Commitment management(performance appraisal, training and development, Sharing, compensation)as an independent variable on the competitive advantage(cost, differentiation)as a dependent variable of some pharmaceutical companies in Baghdad.The sample consisted of (79) respondents in a pharmaceutical company.Based on the importance of the research topic to society and its importance to research organizations and their individuals, the analytical and exploratory approach was adopted in conducting this research, and the questionnaire was adopted as a tool for data collection, in addition to using personal interviews and field notes as tools to assist in its collection. Researcher adopted (SPSS V.26), with descriptive statistical methods (Normal distribution test, confirmatory factor analysis , mean, percentages, standard deviation , Pearson correlation coefficient , simple regression coefficient, multi regression coefficient ) to test hypotheses.The drug stores in the city of Baghdad showed its ability to employ the high commitment management in improving its level of competitive advantage, especially through training and performance management, and the level of availability of research variables was good, but the competitive advantage of the stores needed improvement due to environmental pressures, competition and the financial crisis.